2014
DOI: 10.1007/s00383-014-3474-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered cholecyst-derived extracellular matrix: a biomaterial for in vivo autologous bladder muscular wall regeneration

Abstract: The current study confirmed that autologous fragment-seeded CDECM can be considered as a reliable natural collagen scaffold for bladder augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Decellularization and further in vivo application of some scaffolds have been discussed in our previous articles (Kajbafzadeh et al . , , ,b,c; Sabetkish et al . ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Decellularization and further in vivo application of some scaffolds have been discussed in our previous articles (Kajbafzadeh et al . , , ,b,c; Sabetkish et al . ,b).…”
Section: Discussionmentioning
confidence: 99%
“…Cholecyst-derived scaffold (CDS) is a promising scaffold of animal origin that can be used as xenograft for buttressing staples for reinforcing suture lines during abdominal surgery, 16,17 bladder reconstruction, 18 and skin-wound healing. 19 It has been reported that compared with scaffolds isolated from small intestine and urinary bladder, CDS prepared by a non-detergent/enzymatic method contains relatively less residual cellular components.…”
Section: Introductionmentioning
confidence: 99%
“…No evidence of inflammatory response was revealed 12 weeks postoperatively, and after 24 weeks seeded grafts resulted in whole bladder and muscular layer regeneration and in new micro vessel formation, suggesting that fragment-seeded cholecyst-derived ECM can enhance the properties of acellular gallbladder in terms of bladder wall regeneration [147]. Even if a decellularized scaffold seems to be the direct and straightforward solution for tissue engineering of tissues and organs, several issues need to be addressed as well.…”
Section: Bladdermentioning
confidence: 99%